Quality of Education in Madrasah - Ali, Mohammad; Kos, Julie; Lietz, Petra; Nugroho, Dita; Furqon; Zainul, Asmawi; Emilia, Emi (World Bank, Washington, DC, 2017)
The 'Quality of Education in Madrasah' (QEM) study aimed to provide high quality research into various dimensions of quality of education in Indonesian Madrasahs. The study focused on final year students in Islamic Junior Secondary Schools (Madrasah Tsanawiyah, MT). One hundred and fifty MTs were sampled from across Indonesia, with equal numbers selected from Java and the East and West of the country. Systematically selected intact classes were sampled within schools, involving a total of 6,233 students. Eight instruments were developed for use in the study. Four were achievement tests designed to assess performance in Mathematics, Science, Indonesian and English. Australian Council for Educational Research's (ACER's) School Life Questionnaire (SLQ) was used as an affective measure of school quality. ACER developed an instrument to assess student background characteristics, and a Principal Interview Schedule and a School Inventory were also developed by ACER to collect information on MTs. Mean scores showed that students in Java performed better than students in the East and West regions on each of the four achievement tests, with students in the West performing marginally better than students in the East on all tests. The largest correlations between student background factors and achievement across the three regions were observed for number of home resources and study materials available to students.